Modeling and Evaluation of Vibrational Behavior in Functionally Graded Ceramic-Metal Composite Beams - Ziadoon Mohammed Rahi; Hayder H. Khaleel (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
Functionally Graded Materials (FGMs) represent a notable advancement in materials research as they enable the smooth incorporation of distinct characteristics from various materials. This study examines the vibrational characteristics of functionally graded ceramic-metal composite beams via the use of Finite Element Analysis (FEA) in MATLAB. To capture and study the dynamic response of the replicas. The focus of this investigation is on ceramic and metallic materials that are represented by power-law distribution along their length. In order to include material variation in the global mass and stiffness matrices, the beam segments have been divided into many sections. In this regard, the objective was to calculate natural frequencies and mode shapes of these beams using eigenvalue problems. Results obtained reveal that MATLAB is a reliable tool for investigating dynamic properties of Functionally Graded Materials (FGMs) because it has proven to be user-friendly as well. The present work shows how to use functionally graded indices and porosity on vibration characteristics of composite beams.